El asesinato del sábado por la mañana : un caso psicoanalítico - Gur, Batya; Corniero, María; Gur, Batya (Madrid : Siruela, 2014)
When a well-respected analyst is found dead at the Jerusalem Psychoanalytic Society headquarters, Chief Inspector Michael Ohayon is hired to infiltrate the complex society and find the killer.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Ohayon, Michael -- (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Psychoanalysts -- Fiction; Police -- Israel -- Fiction; Israel -- Fiction; Detective and mystery fiction; Psychological fiction; Electronic books